CUSTOMER RELATIONSHIP MANAGEMENT (CRM) UNTUK PRODUK APLIKASI HOTELMU BERBASIS WEBSITE - Nur Alamsyah (FKOM UNIKU, 2020)
This research aims to build information systems Customer Relationship Management for the Hotelmu Products in managing customers data, proposals data, contracts data and invoicing data. Information systems and Customer Relationship Management are also expected to facilitate the Hotelmu customers’ application to convey complaints, suggestions and criticism. This information system will be designed and built with the Prototype process models and methods of object oriented development. To describe the results of analysis by Object Oriented approach to these compilers uses Unified Modeling Language (UML), among others, Use Case diagrams, Activity diagrams, Sequence Diagrams, and Class diagrams. Then it will be built with CodeIgniter programming language and MySQL as database. Information system Customer Relationship Management (CRM), is expected to ease the controlling all Hotelmu clients effectively and efficiently. So the recapitulation process of client data, making proposals, contracts, and invoices use a special application, and the data stored in the database safely and it can be searched at any time by efficiently. Keywords : CRM, Hotelmu, Object Oriented, Prototype